Effect of chlorhexidine varnish application on Streptococcus mutans colonisation in adolescents with fixed orthodontic appliances - Attin Rengin; Yetkiner Enver; Aykut-Yetkiner Arzu; Knösel Michael; Attin Thomas (Sciendo, 2013)
Objective: The aim of this prospective study was to evaluate the re-colonisation pattern of Streptococcus mutans (MS) in high-level MS-colonised patients with fixed orthodontic appliances following 40% chlorhexidine varnish application prior to bracket placement.